2011
DOI: 10.1063/1.3604792
|View full text |Cite
|
Sign up to set email alerts
|

Transparent conductive oxides: Plasmonic materials for telecom wavelengths

Abstract: We show that despite of low loss, silver and gold are not suitable for a variety of nanoplasmonic applications in the infrared range, which require compact modes in single-interface plasmonic waveguides. At the same time, degenerate wide-band-gap semiconductors can serve as high-quality plasmonic materials at telecom wavelengths, combining fairly high compactness and relatively low loss. Their plasmonic properties in the near-infrared can be compared to those of gold in the visible range. The same materials ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
127
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 193 publications
(131 citation statements)
references
References 30 publications
0
127
0
Order By: Relevance
“…Recently, metal oxides such as indium-tin oxide (ITO) and aluminium-doped zinc oxide have received interest for their plasmonic response in relation to metamaterials and transformation optics. [8,9] The plasma frequency can be tuned by controlling the electron density using electrical or optical methods, opening up opportunities for nearinfrared electro-optic or optical modulators [7,10,11] and sensing devices. [12,13] Pioneering studies by Franzen and co-workers have investigated the plasmonic response of ITO and ITOgold hybrid structures in the metallic (negative epsilon) regime of ITO.…”
mentioning
confidence: 99%
“…Recently, metal oxides such as indium-tin oxide (ITO) and aluminium-doped zinc oxide have received interest for their plasmonic response in relation to metamaterials and transformation optics. [8,9] The plasma frequency can be tuned by controlling the electron density using electrical or optical methods, opening up opportunities for nearinfrared electro-optic or optical modulators [7,10,11] and sensing devices. [12,13] Pioneering studies by Franzen and co-workers have investigated the plasmonic response of ITO and ITOgold hybrid structures in the metallic (negative epsilon) regime of ITO.…”
mentioning
confidence: 99%
“…This is also consistent with our earlier report for Indium Tin Oxide (ITO). 8 Note that the corresponding plasma frequency, which depend on target compositions, substrate temperatures, atmosphere in a chamber, and annealing, are within the range of reported values. 15 Taking into account the above NIR frequency range, the AZO/SiO 2 /p-Si diode device was illuminated with light in the range of NIR frequencies using the above configuration and the current and voltage characteristics are shown in Fig.…”
mentioning
confidence: 66%
“…However, it was recently found that wide band gap semiconductor such as Ga or Al doped ZnO (AZO) and other transparent conductive oxides (TCOs) are potential candidates to replace silver and gold in plasmonic applications. [8][9][10] We have demonstrated that the doped degenerate wide-band-gap semiconductors can be efficient nanoplasmonic materials in the near-infrared spectral range because of strong confinement of SPPs, low loss, and metallic behavior. 8,11,12 Because semiconductors do not have bound-state absorption transitions in their band-gaps, their SPP losses can be even smaller in the near infrared (NIR) region than those in conventional plasmonic materials at corresponding visible wavelengths.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This is much lower than conventional Au and Ag (>10), and even lower than metal nitrides (>20) in the similar wavelengths regime. [19][20][21]. The plasmonic reflection behavior was also investigated in the microwaves or terahertz (THz) regime.…”
Section: E) Heterolayered Al-doped Zno Composites As Transparent Thermentioning
confidence: 99%